Performance evaluation of asphalt mixture using styrene-butadiene-styrene additive - Nguyen, Tuan Anh; Nguyen, Van Long; Le, Ngoc Quang (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2025)
This study investigates the influence of Styrene-Butadiene-Styrene (SBS) polymer modification on the performance characteristics of AC 12.5 asphalt concrete mixtures using Vietnamese aggregate materials. While SBS has demonstrated effectiveness in enhancing asphalt mixture properties globally, comprehensive assessments under Vietnamese conditions with local materials remain limited. Experimental specimens were fabricated with SBS contents of 0% (control), 3%, 5%, and 7% by weight of bitumen, with a constant optimal bitumen content of 5.0%. Performance evaluation was conducted through Marshall stability tests, indirect tensile strength measurements, and Hamburg Wheel-Tracking Device (HWTD) rutting resistance assessments. Results indicate that SBS modification significantly enhances mechanical properties, with optimal performance observed at 5% SBS content. At this concentration, Marshall stability at 60°C increased by 11.1% (15.0 kN vs. 13.5 kN), indirect tensile strength at 25°C improved by 96.4% (2.20 daN/cm² vs. 1.12 daN/cm²), and rutting resistance exhibited a remarkable 57.7% reduction in rutting depth (3.31 mm vs. 7.82 mm) after 15,000 loading cycles at 50°C. The research confirms that SBS modification at 5% content represents an optimal balance between enhanced performance and practical application for AC 12.5 mixtures under Vietnamese conditions, thereby establishing a scientific basis for the implementation of polymer-modified asphalt in Vietnamese road construction practice.